Observations on the distribution and biology of a few bathypelagic fishes from the South-West Coast of India - Mathew, Grace; Jayasankar, P; Sivakami, S; Narayanaswami, J (Indian Journal of Fisheries, 2011)
The coastal fish production is stagnatingduring the last few years (James et al.1987). The only way to increase marine fishproduction is to exploit the untapped resourcesfrom the deeper parts of the EEZ.FORV Sagar Sampada carried out trawlingsurveys to locate and estimate the abundanceof the deep sea resources, especially thecrustaceans and fishes along the upper continentalslope off K.erala c_ during January-February 1988. The present paper dealswith some of the important observations inthis survey.